Theoretical study on the deglycosylation mechanism of rice BGlu1 β‐glucosidase. Issue 8 (13th April 2012) - Wang, Jinhu; Hou, Qianqian; Sheng, Xiang; Gao, Jun; Liu, Yongjun; Liu, Chengbu
Abstract It is proposed that the catalysis of GH1 enzymes follows a double‐displacement mechanism involving a glycosylation and a deglycosylation steps. In this article, the deglycosylation step was studied using quantum mechanical/molecular mechanical (QM/MM) approach. The calculation results reveal that the nucleophilic water (Wat1) attacks to the anomeric C1, and the deglycosylation step experiences a barrier of 21.4 kcal/mol from the glycosyl‐enzyme intermediate to the hydrolysis product, in which an oxocarbenium cation‐like transition state (TS) is formed. At the TS, the covalent glycosyl‐enzyme bond is almost broken (distance of 2.45 Å), and the new covalent bond between the attacking oxygen of the water molecule and C1 is basically established (length of 2.14 Å). In addition, a short hydrogen bridge is observed between the nucleophilic E386 and the C2OH of sugar ring (distance of 1.94 Å) at the TS, which facilitates the ring changing from a chair form to half‐chair form, and stabilizes the oxocarbenium cation‐like TS. © 2013 Wiley Periodicals, Inc.